Numerical simulation of solid–liquid food mixture in a high pressure processing unit using computational fluid dynamics - Abdul Ghani, A.G.; Farid, M.M. (Journal of food engineering, 2007)
Temperature distribution, velocity and pressure profiles during high pressure compression (500 MPa) of liquid food (water) and solid–liquid food mixture (beef fat and water), within a three dimensional cylinder basket is simulated. The computations domain in both cases was performed for a cylinder with a diameter of 38 mm and height of 290 mm, which are the same dimensions of the high pressure unit “FOOD-LAB model S-FL-850-9-W” available at the University of Auckland, New Zealand. The governing equations for continuity, momentum and energy conservation are solved using a commercial computational fluid dynamics (CFD) package (PHOENICS), version 3.5, which is based on a finite volume method of solution. The simulation for liquid food only shows the effect of forced and free convection flow on the temperature distribution in the liquid at the early stages of compression. This is due to the difference between the velocity of the pumping fluid as it enters the cylinder inlet hole (10 −2–10 −3) m s −1 and the velocity in the treatment chamber (10 −8–10 −9) m s −1. The simulation for the solid–liquid mixture shows as well, the temperature distribution in the solid and liquid at different stages of compression. It shows that the solid pieces are more heated than the liquid, which is due to the difference in their compression heating coefficient. Validation of the computed temperature in both cases is found to be in an agreement with those measured experimentally and reported in the literature.